2021
DOI: 10.17576/geo-2021-1702-05
|View full text |Cite
|
Sign up to set email alerts
|

Reducing food waste at school canteens: The behaviour of school communities

Abstract: Efforts to achieve effective food waste management at the school level can be enhanced by knowing the consumers' behavioural aspects, such as the determinants, perception, and driving force behind food waste. However, most of the previous studies tend to focus on household behavioural aspects in food waste management rather than in the context of hospitality, much less at the school canteen level. The objective of this study is to investigate the behaviours of food waste management among school communities. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Three-quarters of the respondents (75%) agreed that the practice of recovering value-added ingredients is good for the environment in the long run. Kasavan et al (2021) reported that Malaysian primary and secondary school students together with educators were aware of the definition of food waste, the environmental implication of mismanagement of food waste and their personal responsibilities towards the environment. This signifies that Malaysian school students were educated about food waste at an early age.…”
Section: Resultsmentioning
confidence: 99%
“…Three-quarters of the respondents (75%) agreed that the practice of recovering value-added ingredients is good for the environment in the long run. Kasavan et al (2021) reported that Malaysian primary and secondary school students together with educators were aware of the definition of food waste, the environmental implication of mismanagement of food waste and their personal responsibilities towards the environment. This signifies that Malaysian school students were educated about food waste at an early age.…”
Section: Resultsmentioning
confidence: 99%
“…Challenges are not only in Brazilian school canteens but rather globally with different options to explore including already proposed changes. No matter of nations, religion, school size, country size, or other demographic parameters, we can find everywhere around the globe same challenge [12][13][14][15][16][17]. With less and less found availability and more population, food management and waste management will become one of the key topics for survival and proper mental and physical development of children.…”
Section: Number Of Mealsmentioning
confidence: 99%